SEROPREVALENCE OF BOVINE BRUCELLOSIS USING INDIRECT ELISA IN QUETTA BALOCHISTAN, PAKISTAN - M. Shafee; M. Rabbani; M. U. D. Ahmad; K. Muhammad; A. A. Sheikh; M; A Awan; M. Z. Shabbir (Journal of Animal and Plant Sciences, 2012)
Brucellosis is considered the most important zoonosis worldwide with high prevalence among livestock. A total of 780 cattle (n = 405) and buffalo (n = 375) serum samples were collected from abattoir Quetta, Balochistan and evaluated for the presence of antibrucella antibodies, using Rose Bengal plate test (RBPT) and indirect enzyme-linked immunosorbent assay (i-ELISA) respectively. The overall prevalence of 3 % and 3.20 % was recorded through RBPT and i-ELISA respectively. In samples collected from cattle (n=405) the higher seroprevalence of 3.95 % and 5.9 % was recorded than buffaloes (n= 375) with 2.1% and 0.265 using RBPT and i-ELISA respectively. Similarly a relatively higher seroprevalence of was found in female animals as 3.72 % and 3.88 % using RBPT and ELlSA respectively. While the prevalence in male was 0.6% using both the test. These results revealed that RBPT and ELISA can be used for large scale screening of brucella antibodes in animals. These findings suggest an alarming situation of bovine brucellosis in animals slaughtered at Quetta abattoir in Balochistan.
Keywords: Brucellosis; Buffalo; Milk Ring Test; indirect enzyme linked immunosorbent assay